2019
DOI: 10.1177/016146811912101305
|View full text |Cite
|
Sign up to set email alerts
|

Sometimes Leaving Means Staying: Race and White Teachers’ Emotional Investments

Abstract: Emotional praxis is not a phrase usually associated with teaching and teacher education. Yet when race enters educational spaces, emotions frequently run high. In particular, Whites are often ill-equipped to handle emotions about race, either becoming debilitated by them or consistently evading them. Without critically understanding the relationship between race and emotions—or, simply, racialized emotions—teachers are unprepared to teach one of the most important topics in modern education. This chapter addre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…While our journey has only begun, our reflective dialogue and self-study has reaffirmed our commitment to “taking emotion seriously.” If as Leonardo and Gamez-Djokic (2019) suggest, teachers are unprepared to teach about race without “critically understanding the relationship between emotion and race” (p. 1), we must continue to deepen our understanding of emotion and its role in teaching and learning social studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While our journey has only begun, our reflective dialogue and self-study has reaffirmed our commitment to “taking emotion seriously.” If as Leonardo and Gamez-Djokic (2019) suggest, teachers are unprepared to teach about race without “critically understanding the relationship between emotion and race” (p. 1), we must continue to deepen our understanding of emotion and its role in teaching and learning social studies.…”
Section: Discussionmentioning
confidence: 99%
“…Leonardo and Gamez-Djokic (2019) suggest that without “critically understanding the relationship between emotion and race, teachers are unprepared to teach about race” (p. 1). Understanding the relationship between emotion and race is a complicated, uncomfortable and contentious process.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, whereas Hispanic and Black students comprise 27% and 15%, respectively, of the student population, only 9% of the teacher population identify as Hispanic and 7% as Black; Asian American and Pacific Islander, American Indian/Alaska Native, and multiracial student enrollment also exceeds the employment of teachers sharing these backgrounds (De Brey et al, 2021). These patterns raise important equity concerns, particularly since the severity of the teacher shortage is greater in low‐resourced schools (Garcia & Weiss, 2019), teacher qualifications are strikingly different across schools (Lankford et al, 2002), teachers experience inequitable hiring and access to all schools (D'amico et al, 2017), and prior research has identified race/ethnicity as a critical, underlying component of teacher−student interactions (Dee, 2005; Leonardo & Gamez‐Djokic, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research examining school settings where congruence exists between minoritized students and teachers has found positive outcomes for students in the areas of achievement, attendance, and self‐reported satisfaction of minority students (Gershenson et al, 2016; Grissom et al, 2015). Conversely, racial/ethnic incongruence has been linked to many potential sources of demand associated with teaching, such as student discipline (Blake et al, 2016), learning outcomes (Dee, 2005; Egalite et al, 2015), engagement in conversations about race (Leonardo & Gamez‐Djokic, 2019), and relationships with colleagues (Coffey & Farinde‐Wu, 2016). Regarding student outcomes, extant research is inconclusive on whether teacher‐student race/ethnicity match corresponds to positive student outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%